Lin28 is a critical factor in the function and aging of Drosophila testis stem cell niche - Sreejith, Perinthottathil (Aging (Albany NY), 2019)
Age-related decline in stem cell function is observed in many tissues from invertebrates to humans. While cell intrinsic alterations impair stem cells, aging of the stem cell niche also significantly contributes to the loss of tissue homeostasis associated with reduced regenerative capacity. Hub cells, which constitute the stem cell niche in the Drosophila testis, exhibit age-associated decline in number and activities, yet underlying mechanisms are not fully understood. Here we show that Lin28, a highly conserved RNA binding protein, is expressed in hub cells and its expression dramatically declines in old testis. lin28 mutant testes exhibit hub cell loss and defective hub architecture, recapitulating the normal aging process. Importantly, maintained expression of Lin28 prolongs hub integrity and function in aged testes, suggesting that Lin28 decline is a driver of hub cell aging. Mechanistically, the level of unpaired (upd), a stem cell self-renewal factor, is reduced in lin28 mutant testis and Lin28 protein directly binds and stabilizes upd transcripts, in a let-7 independent manner. Altogether, our results suggest that Lin28 acts to protect upd transcripts in hub cells, and reduction of Lin28 in old testis leads to decreased upd levels, hub cell aging and loss of the stem cell niche.